HEALTH PASTORAL CARE - Carolus Boromeus Kusmaryanto (P3TK, Sanata Dharma University, 2016)
In her long history, the Churchalways gives special attention to the sick and sufferings, in order to be present in all human condition. Pastoral care is offered for the sick, especially for those who are in the terminal ill. Health Pastoral Care wants to emphasize this point. Health pastoral care is very important in health services, especially in the Catholic healthcare institution. It serves not only the patients and their family but also the entire healthcare personals. Their main role is providing religious and spiritual assistance. In the recent time, their role is even wider, including social and psychological assistance. The Church is very supportive to this pastoral care. Health Pastoral care is an integral part of the Churchs mission to proclaim the Kingdom of God.